English Language Learning and Teaching Through Service Learning: A Phenomenological Study - Hendriks, Anne Lou M. (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
Service-learning is deemed not only to develop students’ attributes and personal development but also to advance students’ learning through its positive influence. However, though their relationships are substantiated in much research, little is known about the contributions service-learning gives towards teaching English to young learners. The findings of this phenomenological study, with tertiary student-teachers as participants, revealed that service-learning could be a vital learning and teaching catalyst. It highlights pedagogical insights of an effective instructional strategy that enhances personal, emotional, and professional growth. Keywords : Service-learning, English language learning and teaching, young learners, instructional strategies, Indonesia